Strategi Kepala Sekolah Dalam Mengelola Konflik Antara Guru Di Sekolah Dasar - Rosi Novelia Cahyani; Minarti Agustina; Eno Astriyani; Mutoharoh Mutoharoh (Journal of Innovative and Creativity, 2025)
This study aims to examine the strategies of school principals in managing conflicts between teachers at SDN Sukajadi 2, Carita District, Pandeglang Regency. Using a qualitative approach with a case study design, this research focuses on gaining an in-depth understanding of the forms of conflict, the principal's role, and the effectiveness of the strategies implemented in creating a harmonious work environment. Data were collected through in-depth interviews, direct observation, and documentation studies, then analyzed using the Miles and Huberman model. The research findings indicate that conflicts between teachers are generally in the form of task, communication, and personal conflicts, most of which are mild but have the potential to cause tension if not resolved promptly. The principal plays an active role as a mediator, counselor, and visionary leader by implementing collaborative and persuasive strategies, establishing clear work rules, and task rotation. These strategies have proven effective in reducing the number of recurring conflicts, increasing teacher participation, satisfaction, and morale, and maintaining the quality of the learning process. This finding emphasizes the importance of school principal leadership in conflict management to support the creation of a conducive work environment and improve the quality of education in elementary schools.